2006
DOI: 10.1152/ajpheart.01307.2005
|View full text |Cite
|
Sign up to set email alerts
|

ANG II-induced cardiac molecular and cellular events: role of aldosterone

Abstract: Chronic elevation of circulating ANG II is associated with cardiac remodeling in patients with hypertension and heart failure. The underlying mechanisms, however, are not completely defined. Herein, we studied ANG II-induced molecular and cellular events in the rat heart as well as their links to the redox state. We also addressed the potential contribution of aldosterone (ALDO) on ANG II-induced cardiac remodeling. In ANG II-treated rats, and compared with controls, we found: 1) the expression of proinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 26 publications
7
44
1
Order By: Relevance
“…ANG II infusion in mice also reduces the total SOD activity in plasma, aorta and kidney cortex as well as the mRNA and protein expression for EC-SOD [102]. Compared to the normal rat heart, gp91 phox mRNA is largely increased within the perivascular and microscopic injury in both ventricles in ANG II-treated rats and cells expressing gp91 phox at these sites were primarily inflammatory cells; cardiac Mn-SOD and catalase protein levels, however, remain unchanged in ANG II-infused rats [103]. In ANG IIinfused mice the aorta mRNA and protein expression of EC-SOD as well as the EC-SOD activity is increased, while the CuZn-SOD protein expression is unchanged [104].…”
Section: Ang Ii-induced Effect On Superoxide Dismutase Activity In Camentioning
confidence: 95%
See 1 more Smart Citation
“…ANG II infusion in mice also reduces the total SOD activity in plasma, aorta and kidney cortex as well as the mRNA and protein expression for EC-SOD [102]. Compared to the normal rat heart, gp91 phox mRNA is largely increased within the perivascular and microscopic injury in both ventricles in ANG II-treated rats and cells expressing gp91 phox at these sites were primarily inflammatory cells; cardiac Mn-SOD and catalase protein levels, however, remain unchanged in ANG II-infused rats [103]. In ANG IIinfused mice the aorta mRNA and protein expression of EC-SOD as well as the EC-SOD activity is increased, while the CuZn-SOD protein expression is unchanged [104].…”
Section: Ang Ii-induced Effect On Superoxide Dismutase Activity In Camentioning
confidence: 95%
“…In ANG II-infused rat kidney a 50% decrease in Mn-SOD activity is observed [108], while Chabrashvili et al [101] reported an increased mRNA expression of Mn-SOD in the kidney cortex of ANG IItreated rats. An unchanged Mn-SOD protein expression is found in cardiac [103] and kidney [108] tissue of ANG IIinfused rats, while a reduced renal Mn-SOD protein level is found in ANG II-treated rats [109]. In ANG II-infused mice, the aortic protein level Mn-SOD is unchanged, but declines in extracellular SOD deficient mice [110].…”
Section: Down-regulation Of Mn-sod By Angio-tensin II In Cardiac Fibrmentioning
confidence: 95%
“…Both cardiomyocytes and fibroblasts express MRs with high affinity for both corticosterone and aldosterone (110,181,157). The inflammatory effects of coricosterone and aldosterone in the heart are partly mediated by an interaction with the RAAS as well as effects directly mediated through MR activation (39,55,56,73,90,167,168,170,196,238). For example, in rats treated with aldosterone and high dietary salt, the AT 1 R expression and ventricular density of the AT 1 R have been observed to increase (90).…”
Section: Mineralocorticoids In the Heartmentioning
confidence: 99%
“…After exposure, the film was developed and sections were stained with hematoxylin and eosin. Quantitation of mRNA optical density was performed using a computer image analysis system (NIH Image, 1.60) (23).…”
Section: In Situ Hybridizationmentioning
confidence: 99%